Reflectivity of second-year Arctic sea ice: Findings from the MOSAiC expedition - Semmling, Maximilian; Wickert, Jens; Kreß, Frederik; Hoque, Mohammed Mainul; Divine, Dmitry V.; Gerland, Sebastian; Spreen, Gunnar (2021)
Sea ice is a crucial parameter of the Earth climate system. Its high albedo compared to water influences the oceans' radiation budget significantly. The importance of monitoring arises from the high variability of sea-ice state and amount induced by seasonal change and global warming. GNSS reflectometry can contribute to global monitoring of sea ice with high potential to extend the spatiotemporal coverage of today's observation techniques. Properties like ice salinity, temperature and thickness can affect the signal reflection. The MOSAiC expedition (Multidisciplinary drifting Observatory for the Study of Arctic Climate) gave us the opportunity to conduct reflectometry measurements under different sea-ice conditions in the central Arctic. A dedicated setup was mounted, in close cooperation with the Alfred-Wegener-Institute (AWI), on the German research icebreaker Polarstern that drifted during nine months with the Arctic sea ice. We present results from the expedition's first leg in autumn 2019. They refer to the Siberian Sector of the Arctic (from about 85°N to 87°N). Profiles of sea-ice reflectivity over elevation angle (range: 1° to 45°) are derived with daily resolution considering reflection data recorded at left-handed (LH) and right-handed (RH) circular polarization. Respective predictions of reflectivity are based on reflection models of bulk sea ice or a sea-ice slab. The latter allows to include the effect of signal penetration down to the underlying water. Results of comparison between LH profiles and bulk model confirm a reflectivity decreases (about 10 dB) when surrounding water vanishes and the ship drifts in compact sea ice. Second-year ice was the primary ice type reported by ancillary observations for the drifting period of the ship (first leg). Based on the LH profiles, relative sea-ice permittivity is estimated, assuming a bulk medium. The results (typically below 3) indicate an old ice type (second-year or multiyear ice) in agreement with the ancillary observations. Some days with higher ...